Development of Animated Video-Based Mathematics Learning Media Using Adobe After Effect on The Three-dimensional Material to Improve Mathematical Literacy - Firdaus, Dhiya Fathiyyah; Suripah, Suripah; Angraini, Lilis Marina (Kreano, Jurnal Matematika Kreatif-Inovatif, 2023)
This article discusses the development of animation-based learning videos on three-dimensional materials to improve mathematical literacy. This development research uses the Plomp model, that is, preliminary research, development or prototyping, and assessment phase. The results of the learning video in this development are viewed under three aspects, namely validity, practicality, and effectiveness, involving students of SMA Negeri 3 Pekanbaru as research subjects. The animated video-based learning media was declared very valid with a result of 73, very practical with a result of 56, and effective in improving mathematical literacy. This states that animation-based video learning media is good and worthy of being used as a mathematics learning media to improve mathematical literacy.Artikel ini membahas pengembangan video pembelajaran berbasis animasi pada materi tiga dimensi untuk meningkatkan literasi matematika. Penelitian pengembangan ini menggunakan model Plom, yaitu tahap penelitian pendahuluan, pengembangan atau prototyping, dan penilaian. Hasil video pembelajaran dalam pengembangan ini dilihat dalam tiga aspek, yaitu validitas, kepraktisan, dan efektivitas, dengan melibatkan siswa SMA Negeri 3 Pekanbaru sebagai subjek penelitian. Media pembelajaran animasi berbasis video dinyatakan sangat valid dengan hasil 73, sangat praktis dengan hasil 56, dan efektif dalam meningkatkan literasi matematika. Hal ini menyatakan bahwa media pembelajaran video berbasis animasi baik dan layak digunakan sebagai media pembelajaran matematika untuk meningkatkan literasi matematika